Appropriate dietary phosphorus levels promote growth performance, mineral retention, and hepatic lipid metabolism in juvenile American eels (Anguilla rostrata) - Yichuang Xu; Shuo Wang; Xinyu Hu; Pan Wang; Xiaozhao Han; Jinyue Yang; Ying Liang; Shaowei Zhai (Aquaculture Reports)
Phosphorus (Pi) is an essential mineral for fish and exerts critical roles in growth, metabolism, and skeletal development. The present research was carried out to investigate the effects of different dietary Pi levels on the growth performance, minerals retention, and hepatic lipid metabolism of juvenile American eels. Five experimental diets were prepared using NaH2PO4 and KH2PO4 as Pi sources, with total Pi levels in the diets were determined to be 0.52 %, 0.90 %, 1.31 %, 1.71 %, and 2.11 %, respectively. The feeding trial was conducted over a period of 10 weeks. In comparison to eels fed diets containing 0.52 % Pi, those fed diets with 1.31 % Pi exhibited improved growth performance, feed utilization, and whole-body retention of calcium, Pi, copper, iron, and zinc. Additionally, Eels fed diets containing 1.31 % Pi had lower deformity rate, serum lipid content, and hepatic lipid levels than those receiving diets with 0.52 % Pi. Dietary Pi addition promoted hepatic lipolysis while inhibited hepatic lipogeneses. Conversely, eels fed diets with 2.11 % Pi showed reduced growth performance, feed utilization, and minerals retention, alongside a higher deformity rate, compared to those fed diets containing 1.31 % Pi. Lipidomic analysis indicated that, compared to eels fed diets containing 0.52 % Pi, autophagy, glycerophospholipid metabolism, glycosylphosphatidylinositol metabolism, α-linolenic acid metabolism, and arachidonic acid metabolism were enhanced in the liver of those fed diets with 1.31 % Pi. The quadratic regression analysis of weight gain rate, feed efficiency, and Pi retention against the dietary Pi levels indicated optimal dietary Pi levels for American eels range from 1.31 % to 1.40 %. These findings offer critical insights into dietary Pi supplementation and underscoring the importance of optimal dietary Pi levels for American eels.